Pro-inflammatory Actions of Heme and Other Hemoglobin-Derived DAMPs - Bozza, Marcelo T.; Jeney, Viktória (Frontiers in Immunology, 2020)
Damage associated molecular patterns (DAMPs) are endogenous molecules originate from damaged cells and tissues with the ability to trigger and/or modify innate immune responses. Upon hemolysis hemoglobin (Hb) is released from red blood cells (RBCs) to the circulation and give a rise to the production of different Hb redox states and heme which can act as DAMPs. Heme is the best characterized Hb-derived DAMP that targets different immune and non-immune cells. Heme is a chemoattractant, activates the complement system, modulates host defense mechanisms through the activation of innate immune receptors and the heme oxygenase-1/ferritin system, and induces innate immune memory. The contribution of oxidized Hb forms is much less studied, but some evidence show that these species might play distinct roles in intravascular hemolysis-associated pathologies independently of heme release. This review aims to summarize our current knowledge about the formation and pro-inflammatory actions of heme and other Hb-derived DAMPs.